PROGRAM KERUCUT ORDE DUA - , ZEKI GUNAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In this final project, we discuss about second order cone programming, alge braic properties of second order cone, and primal-dual interior point algorithm for second order cone programming. On the topic of second order cone programming, we discuss about second order cone and cartesian product of several second order cones which both of them are convex, cone, and pointed set with nonempty interior point. Moreover, we give a general form of primal-dual second order cone program ming and some properties that can be obtained for the primal-dual second order cone programming. On the topic of algebraic properties of second order cone, we discuss about the space R n with binary operation â¦. In space (R n , â¦), we can find relation between (R n , â¦) and second order cone. Furthermore, the binary operation â¦ is ex tended into â¦ r , so that (R n , â¦ r ) has relation with cartesian product of several second order cones. Based on the algebraic properties of second order cone, we study about the primal-dual interior point algorithm for solve the primal-dual second order cone programming problems and analysis of the algorithm.